Comparative Physicochemical Screening and Toxicology of Hydroethanol Extracts of the Parts of Pterocarpus santalinoides l’Hér. ex DC. (Fabaceae) in Wistar Rats - Aimé Cézaire T. Ayéna; Kossivi Dosseh; Kokou Idoh; Amegnona Agbonon; Messanvi Gbeassor (The Scientific World Journal)
Aims. The aim of this study was to compare the phytochemical profile and acute and chronic toxicity of hydroethanolic extracts of three parts of P. santalinoides. Methods. Seven major chemical groups (alkaloids, flavonoids, saponosides, coumarins, tannins, triterpenes, and steroids) were studied. The single dose limit test of 5000 mg/kg body weight was used to evaluate the acute toxicity of each organic extract. Subacute toxicity was evaluated after daily oral doses of 500 and 1000 mg/kg body weight were administered to rats for 28 days. Results. At a single dose of 5000 mg/kg, none of the extracts (leaf, trunk bark, and root) caused death in experimental rats. However, the trunk bark extract of P. santalinoides induced coat change and lethargy in treated rats. Macroscopic observation of the internal organs (liver and kidneys) of the rats showed no abnormalities. In the subacute test, only the trunk extracts induced signs of toxicity such as mobility disorders, diarrhea, and loss of body weight at a dose of 1000 mg/kg. Conclusion. This study showed that the hydroethanol extracts of the leaves, trunk bark, and root bark of P. santalinoides divergently concentrated the main chemical groups of interest. Administration of a single dose of extracts from all three P. santalinoides is not toxic to the consumer. However, when used over a long period of time, they can have a harmful effect on the consumer. In view of the different results of the trunk bark extract and in a context of conservation of the species, we recommend the use of the hydroethanolic extract of the leaves in the different treatments in which the three organs are involved.